Strategi Promosi Masal untuk Meningkatkan Penjualan dan Market Share - Fajar Suryatama (Jurnal Ilmiah Aset, 2018)
This research tries to apply promotional strategy with mass promotion methods (mass promotion) that communicate with potential consumers at the same time. Factors that encouraged this method because the shops/Dealers still recently opened and is located in a location far from the city centre so that less known local community. The main purpose of the application of this strategy is to make the dealership and its products more quickly recognized so that the sales and market share can be improved.